Challenges in Implementing ICT Solutions in Low-Income Schools - Sucipto, Purwo Agus; Zaki, Amin; Lima, Lucas (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
The integration of Information and Communication Technology (ICT) in education has been widely recognized for its potential to improve teaching and learning outcomes. However, low-income schools face unique challenges in implementing ICT solutions, which can hinder their effectiveness. This research explores the barriers and opportunities associated with the implementation of ICT in low-income schools. The study aims to identify the key factors influencing the adoption and integration of ICT, including infrastructure limitations, teacher preparedness, and access to resources. A mixed-methods approach was employed, involving both qualitative and quantitative data collection. Surveys were distributed to teachers and administrators from low-income schools, while interviews provided deeper insights into the contextual challenges faced by these institutions. Data analysis was conducted using SPSS to identify statistical trends, while thematic analysis was applied to the qualitative data. The findings revealed that inadequate infrastructure, such as a lack of reliable internet access and outdated equipment, is a significant barrier to ICT adoption. Furthermore, limited training for teachers in the effective use of ICT tools hampers their integration into the curriculum. Despite these challenges, the study identified potential opportunities for overcoming these barriers, including government support and community partnerships. In conclusion, the successful implementation of ICT in low-income schools requires addressing infrastructure gaps and enhancing teacher training programs. Strategic partnerships and policy interventions are crucial in ensuring that these schools can leverage the benefits of ICT to improve educational outcomes.